2022
DOI: 10.3390/children9040553
|View full text |Cite
|
Sign up to set email alerts
|

Thriving despite Parental Physical Abuse in Adolescence: A Two-Wave Latent Transition Analysis on Hedonic and Eudaimonic Violence-Resilience Outcome Indicators

Abstract: Internationally, about 25% of all children experience physical abuse by their parents. Despite the numerous odds against them, about 30% of adolescents who have experienced even the most serious forms of physical abuse by their parents escape the vicious family violence cycle. In this study, we analyzed longitudinally the data from a sample of N = 1767 seventh-grade high school students in Switzerland on physical abuse by their parents. We did this by conducting an online questionnaire twice within the school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 122 publications
4
35
0
8
Order By: Relevance
“…Cameranesi [55], who specifically examined IPV exposure from a psychopathology perspective, found four adjustment profiles: resilient, multiple severe problems, multiple mild problems, and externalizing problems. Kassis et al [10] also found four resilience and well-being patterns despite physical parental violence experiences, which they based on the dual-factor model of mental health, which include the resilient, troubled, vulnerable, and non-resilient. Janousch et al [56], who examined resilience trajectories in Switzerland without accounting for risk factors, found three trajectories: resilient, non-resilient, and untroubled.…”
Section: Resilience Trajectories Of Youth's Ipv Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Cameranesi [55], who specifically examined IPV exposure from a psychopathology perspective, found four adjustment profiles: resilient, multiple severe problems, multiple mild problems, and externalizing problems. Kassis et al [10] also found four resilience and well-being patterns despite physical parental violence experiences, which they based on the dual-factor model of mental health, which include the resilient, troubled, vulnerable, and non-resilient. Janousch et al [56], who examined resilience trajectories in Switzerland without accounting for risk factors, found three trajectories: resilient, non-resilient, and untroubled.…”
Section: Resilience Trajectories Of Youth's Ipv Exposurementioning
confidence: 99%
“…Youths are at a significant risk of lifelong neg-ative consequences that are also reflected in society [7,8], with intimate-partner violence (IPV) exposure being one of the most common familial burdens for them [9]. Violence resilience refers to a process whereby individuals develop adaptively despite experiences of violence that lead to the significantly increased likelihood of negative socio-emotional consequences [10]. According to Masten [11], resilient outcomes are characterized by competence at age-specific developmental tasks as well as an absence of psychopathological symptoms, despite risk exposure.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue features 18 articles that examine family risk and resilience among children and adolescents across developmental stages, ranging from early childhood to late adolescence/young adulthood. A wide range of child outcomes are examined in these studies, including children’s use of electronic devices [ 1 , 2 ], maltreatment experiences [ 3 ], mental health [ 4 , 5 , 6 , 7 ], school readiness and academic functioning [ 8 ], suicidal thoughts and behaviors [ 9 ], socioemotional development [ 10 , 11 , 12 , 13 ], and resilient/adaptive functioning [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…Looking beyond risk factors, several papers focused on family strengths and protective factors related to childhood resilience. For example, Kassis et al examined hedonic and eudaimonic well-being among adolescents with physical abuse experiences and identified distinct violence-resilient patterns and trajectories [ 14 ]. Not surprisingly, many studies found parenting or other parent-related constructs (e.g., parental relationships, parental support) to be key family protective factors in relation to positive child outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation